2017
DOI: 10.1007/s12178-017-9387-6
|View full text |Cite
|
Sign up to set email alerts
|

Lisfranc injuries

Abstract: Purpose of review The purpose of this review is to discuss key anatomic and pathoanatomic factors, treatment principles, and patient outcomes of Lisfranc injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 20 publications
1
40
0
4
Order By: Relevance
“…12,33 Despite the relative ubiquity of such intervention, there still remains little consensus as to whether removing these implants in staged fashion actually makes a clinical difference, nor a clear guide to the optimal timing for implant removal. 5 When including hardware removal in the analysis, the reoperation rates in this study were comparable to those found in literature (72% in the ORIF group and 27.3% in the PA group). 12 In most cases (n = 83, 71.6% of ORIF cases), hardware was removed because of surgeons’ preference and without correlation to operative infections or wound healing problems ( P = .13 and P = .6, respectively).…”
Section: Discussionsupporting
confidence: 88%
“…12,33 Despite the relative ubiquity of such intervention, there still remains little consensus as to whether removing these implants in staged fashion actually makes a clinical difference, nor a clear guide to the optimal timing for implant removal. 5 When including hardware removal in the analysis, the reoperation rates in this study were comparable to those found in literature (72% in the ORIF group and 27.3% in the PA group). 12 In most cases (n = 83, 71.6% of ORIF cases), hardware was removed because of surgeons’ preference and without correlation to operative infections or wound healing problems ( P = .13 and P = .6, respectively).…”
Section: Discussionsupporting
confidence: 88%
“…Lisfranc injuries are generally associated with high energy mechanisms, for example, fall from a height or motor vehicle accident 1 2. However, they may also occur from relatively lower energy trauma, such as a ground-level fall depending on the positon of the foot.…”
Section: Answer: Bmentioning
confidence: 99%
“…Treatment of Lisfranc injuries depends on the stability of the injury. Poor outcomes, such as collapse of the cuneiform-metatarsal arch and/or intractable midfoot arthritis are common where injuries have been missed 1 2…”
Section: Answer: Bmentioning
confidence: 99%
“…Traditional fixation methods include percutaneous screws, open reduction and internal fixation (ORIF), and primary arthrodesis. 3…”
Section: Introductionmentioning
confidence: 99%